Microbiota does not influence tumor development in two models of heritable cancer - Jessica Spring; Sandeep Gurbuxani; Tatyana Golovkina (mBio)
ABSTRACT Microbial impact on tumorigenesis of heritable cancers proximal to the gut is well-documented. Whether the microbiota influences cancers arising from inborn mutations at sites distal to the gut is undetermined. Using two models of heritable cancer, Trp53-deficient mice and Wnt1-transgenic mice, and a gnotobiotic approach, we found the microbiota to be inconsequential for tumor development. This work furthers our understanding of the degree of the microbial impact on tumor development.IMPORTANCEThe influence of the microbiome on the development of cancer is well-documented with many if not all published studies reporting either a positive or a negative impact. None of the published studies, however, presented data on the influence of the microbiome on the development of heritable cancer. We find that the microbiota has no influence on cancer development in two models of spontaneous cancers driven by germline Trp53 deficiency and constitutive Wnt1 signaling.